(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The present research is to evaluate the psychomotor skills of kabaddi and kho-kho players in the district of Chhattisgarh. Thirty players from Kabaddi and another thirty from Kabaddi were chosen on purpose for the selected study. Ages of participants were from 18 to 22. The gathered data was calculated using the T-test. The results of this investigation confirmed the obvious differences between kabaddi and kho-kho players. The following variables were determined to be significant at the 0.05 level. Conclusions have been made, and the study's findings on speed indicate that participants have significant difference in this area. Players with a Kabaddi: Mean score of 7.67 outperformed those with a kho-kho score :6.09 in every way. The end outcome is agility. The study's findings on agility indicate that participants differed significantly in this area. The Kabaddi Mean players (21.20) outperformed the kho-kho Mean (10.64) players. The study's findings indicate that there were substantial differences among players when it came to balance. Players with a Kabaddi Mean of 28.74 outperformed those with a Kho-kho Mean of 10.71. The study's findings indicate that players differed significantly in terms of flexibility. Players with a Kabaddi Mean of 20.16 outperformed those with a kho-kho Mean of 15.66. The study's findings regarding eye-hand coordination indicate that there were substantial differences between players in this area. Kho-kho Mean (21.02) players weren't as good as Kabaddi Mean (22.71) players.